In search of fair trade: Stories from the field - Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2016)
The narratives of people in this booklet tell the story of how structured trade has changed lives of smallholders in Eastern Africa. It is a story of hope for millions of disadvantaged farmers and for consumers, but it is also a cautionary tale – when a trader in Nakuru lost his access to the local warehouse, the trading system collapsed, to the detriment of farmers, traders and financiers alike. Talk to farmers like those featured in this booklet and you are unlikely to hear the term ‘structured trade’ – this is the language of experts – but there is little doubt that they see how the approach brings many benefits.